查泰莱夫人的情人 ebook Lady chatterley's lover. - Lawrence, D. H. (Bridge Bilingual Classics., 2015)
Lady Chatterley's Lover is a novel by D. H. Lawrence, first published in 1928. The first edition was printed privately in Florence, Italy. It could not be published openly in the United Kingdom until 1960. The book soon became notorious for its story of the physical relationship between a working-class man and an aristocratic woman, its explicit descriptions of sex, and its use of then-unprintable words.The story is said to have originated from events in Lawrence's own unhappy domestic life, and he took inspiration for the settings of the book from Eastwood, Nottinghamshire, where he grew up. According to some critics, the fling of Lady Ottoline Morrell with "Tiger", a young stonemason who came to carve plinths for her garden statues, also influenced the story. Lawrence at one time considered calling the novel Tenderness and made significant alterations to the text and story in the process of its composition. It has been published in three different versions. 《查泰莱夫人的情人》是劳伦斯最后一部长篇小说，1928年7月在佛罗伦萨出版，立刻受到英国文学界的攻击，当局以"有伤风化"的罪名予以查封，直到1960年才得以解禁。小说中的女主人公康妮嫁给了贵族地主查泰莱为妻，但不久他便在战争中负伤，腰部以下终身瘫痪。在老家中，二人的生活虽无忧无虑，但却死气沉沉。庄园里的猎场守猎人重新燃起了康妮的爱情之火及对生活的渴望，她经常悄悄来到他的小屋幽会，尽情享受原始的、充满激情的性......